The influence of leadership on academic scientists' propensity to commercialize research findings - Stefan Krabel; Alexander Schacht (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Previous studies of organizations have highlighted that leadership and organizational performance have a strong and long-term impact on employee behavior in private firms. In this study, we analyze whether similar effects can also be observed in academia by examining the commercialization behavior of academic scientists. The empirical analysis is based on panel data of commercialization for the period of 1980 - 2004 within the Max Planck Society, a leading research organization in Europe. The results suggest that director engagement in disclosure activity and the amount of royalties received lead to a significant increase in invention disclosure the following year. However, we do not find the same results when modeling longer time lags. Thus, academic scientists mimic successful behavior, while leadership behavior does not have long-lasting effects on commercialization behavior within the institute. We conclude that existing organizational theories need to be modified for academic organizations.
Keywords: L24; O33; O39; 330; leadership effect; technology commercialization; Hochschulforschung; Lizenz; Technologietransfer; Innovation; Kommerzialisierung; Wissenschaftler; Führungsstil; Deutschland